2007
DOI: 10.1017/s1121189x00004565
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of socio-economic inequalities on the use of mental health services?

Abstract: Amartya Sen, who received the Nobel Prize for Economics, has demonstrated that the incidence of deprivation, in terms ofcapability, can be surprisingly high even in the most developed countries of the world. The study of socio-economic inequalities, in relation to the utilisation of health services, is a priority for epidemiological research. Socio-economic status (SES) has no universal definition. Within the international research literature, SES has been related to social class, social position, occupational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 26 publications
1
18
0
3
Order By: Relevance
“…Finally, the results of this study indicate that DM sufferers with a low socioeconomic level suffer from a greater delay in diagnosis and are worse at controlling their condition. If this is the case, it would be consistent with the findings of the existing literature, both in terms of patients with other chronic diseases such as cancer (Woods et al 2006, Dejardin et al 2008, HIV (Giuliano & Vella 2007, Tsai et al 2009 or mental illnesses (Bonizzato & Tello 2003, Muntaner et al 2003, Amaddeo & Jones 2007, and also in terms of general health problems (Mackenbach & Bakker 2003, Knight et al 2009).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Finally, the results of this study indicate that DM sufferers with a low socioeconomic level suffer from a greater delay in diagnosis and are worse at controlling their condition. If this is the case, it would be consistent with the findings of the existing literature, both in terms of patients with other chronic diseases such as cancer (Woods et al 2006, Dejardin et al 2008, HIV (Giuliano & Vella 2007, Tsai et al 2009 or mental illnesses (Bonizzato & Tello 2003, Muntaner et al 2003, Amaddeo & Jones 2007, and also in terms of general health problems (Mackenbach & Bakker 2003, Knight et al 2009).…”
Section: Discussionsupporting
confidence: 87%
“…2009) or mental illnesses (Bonizzato & Tello 2003, Muntaner et al. 2003, Amaddeo & Jones 2007), and also in terms of general health problems (Mackenbach & Bakker 2003, Marmot et al. 2008, Knight et al.…”
Section: Discussionmentioning
confidence: 99%
“…In their review, Fryers et al (2003) have identified several studies providing evidence of an association between markers of a less privileged social position (especially unemployment, less education and low income or poor standard of living) and higher prevalence of common mental disorders; moreover, they have also shown that a low SES has a potential to worsen mental disorders; a similar conclusion has been drawn by Amaddeo & Jones (2007); the latter authors have also stated that the precise factors linking SES and service utilization are still unclear.…”
Section: Social Inequalities and Individual Resiliencementioning
confidence: 78%
“…A possible explanation could be that higher educated groups and women might recognise and accept psychiatric needs more than lower educated groups and men [29]. The opposite trend for income might be a sign of minimal financial barriers, but possibly also an expression of negative influence by psychiatric disease on income (social selection) [30]. …”
Section: Discussionmentioning
confidence: 99%